A Systematic Review of Sport Governance Models - Rachmadi, Mochamad Fikri; Ma’mun, Amung; Budiana, Dian (ASEAN Journal of Sport for Development and Peace, 2024)
In the research conducted by Thompson et al (2022), there were research limitations in the use of language during the systematic review search process and the time limit criteria were quite long. Considering the many models in sports governance that have been proposed by academics, this research systematically reviews models in sports governance. Research methods: The method used in this research is a systematic literature review. The steps of a systematic literature review consist of review questions, inclusion criteria, search strategy, selection and assessment, extraction, and synthesis. Results and Findings: In total, there are 30 articles spanning the last 3 years which were used as the main source for this research. The results and findings in this research are still in the form of hypotheses, overall a sports governance model that is transparent, accountable, and democratic is found. Implications: The findings obtained highlight the systematic nature of sports governance. In the sports governance process, academics and practitioners have different points of view when implementing it, which causes academics and practitioners to be incompatible. For this reason, researchers in future studies can use a stronger, evidence-based sports governance model so that practitioners can understand it in more detail.